PENERAPAN ENTERPRISE RESOURCE PLANNING (ERP) DALAM MEMBANGUN SISTEM PENGENDALIAN MANAJEMEN SEBAGAI PENINGKATAN KINERJA PERUSAHAAN - HAJJAR DAMAYANTI, HANINDIA (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACTThe use of Enterprise Resource Planning (ERP) in a company is crucial especially in obtaining information for decision making. Based on observations on some of the companies that have been using ERP, ERP can create synchronization and integration of various function within the company. By implementing ERP, management can build a management control system effectively and efficiently. ERP can help management in overseeing and managing resources that owned by the company are mainly human resources. However the use of ERP is still limited to larger companies that have the readiness fund and resources that needed.Keywords: Enterprise Resource Planning (ERP), Management Control System